Effect of linker moiety on linear dimeric benzotriazole derivatives as highly stable UV absorber for transparent polyimide film. (September 2020) - Kim, Suhyeon; Hwang, Tae Gyu; Namgoong, Jin Woong; Kim, Hong Mo; Kim, Jae Pil
Abstract: In this study, we developed a series of highly stable UV absorbers for polymers which require lengthy high temperature processes, such as polyimide (PI). Three types of linear dimeric hydroxyphenyl benzotriazole derivatives were synthesized by linking monomers with different linker moieties (phenyl, disulfide, biphenyl). The arrangement between the monomers was affected by the type of linker moiety introduced in the dimeric hydroxyphenyl benzotriazole derivatives. As a result, the intermolecular interactions changed resulting in changes in thermal stability and solubility. These results revealed that dimeric hydroxyphenyl benzotriazole derivatives had remarkable stability compared to the monomer. Especially, a novel dimeric UV absorber with phenyl linker (PBT) exhibited excellent stability suitable for high temperature processes. Graphical abstract: Image 1 Highlights: Novel linear dimeric hydroxyphenyl benzotriazole derivatives were synthesized and used as UV absorber for polyimide film. Synthesized dimeric UV absorbers showed higher thermal stability than monomer due to increased intermolecular interactions. A novel compound PBT exhibited excellent thermal stability in transparent polyimide film.